IMMUNOMORPHOLOGIC CHANGES IN TUMOR TISSUE OF PATIENTS WITH BREAST CANCER INDUCED BY NEOADJUVANT CHEMOTHERAPY CARRIED OUT IN ARTIFICIALLY HYPERGLYCEMIC STATE - L. T. Alimkhodzhayeva (Опухоли женской репродуктивной системы)
We reviewed the results of investigation which enrolled 69 patients with locally advanced breast cancer. Patients were divided into two groups. Conventional preoperative multi-agent chemotherapy with Cyclophosphamide, Metotrexate and 5-FU (CMF scheme) was car- ried out to patients of the first group, whereas AC scheme (Doxorubicin and Cyclophosphan) was implemented in the second group. To all participators chemotherapy was given during hyperglycemic state with serum glucose concentration of 14—15 mmol/l. The main purpose of the study is to evaluate the appropriateness of therapy according to the intensity of medical pathomorphosis and level of immunologic defense.